Four new species of Pteronia (Astereae, Asteraceae) from South Africa - Bello, Anifat O.; Boatwright, James S.; van Der Bank, Michelle; Magee, Anthony R. (Phytotaxa, 2020)
During taxonomic studies of the southern African genus Pteronia, four new species, P. armatifolia, P. decurrens, P. flava and P. glandulosa were uncovered from the Northern and Western Cape provinces of South Africa. We formally describe these four new species here and provide detailed descriptions, diagnostic characters, geographical distributions, as well as ecological information for each of the species.